Transmembrane Helices Are an Overlooked Source of Major Histocompatibility Complex Class I Epitopes - Bianchi, Frans; Textor, Johannes; van den Bogaart, Geert (Frontiers in Immunology, 2017)
About a fourth of the human proteome is anchored by transmembrane helices (TMHs) to lipid membranes. TMHs require multiple hydrophobic residues for spanning membranes, and this shows a striking resemblance with the requirements for peptide binding to major histocompatibility complex (MHC) class I. It, therefore, comes as no surprise that bioinformatics analysis predicts an over-representation of TMHs among strong MHC class I (MHC-I) binders. Published peptide elution studies confirm that TMHs are indeed presented by MHC-I. This raises the question how membrane proteins are processed for MHC-I (cross-)presentation, with current research focusing on soluble antigens. The presentation of membrane-buried peptides is likely important in health and disease, as TMHs are considerably conserved and their presentation might prevent escape mutations by pathogens. Therefore, it could contribute to the disease correlations described for many human leukocyte antigen haplotypes.